2015
DOI: 10.1109/tns.2015.2395952
|View full text |Cite
|
Sign up to set email alerts
|

On Few-View Tomography and Staircase Artifacts

Abstract: This paper investigates some potential methods for few-view tomography, and investigates the cause and remedy of the staircase artifacts. This paper also discusses whether there is any benefit to use edge-preserving filters in emission tomography. We formulate a general Green’s one-step-late algorithm, so that it can incorporate any linear or non-linear filters. We argue that the derivative of the penalty function can be “artificially” created, not naturally derived from a penalty function. We have gained more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Reconstruction of the intermediate three‐dimensional activity distribution from a limited number of projections and a limited angular coverage is a challenging task. Iterative algorithms based on total variation minimization have been fairly successful for few‐view CT image reconstruction as well as for SPECT imaging . Total variation minimization encourages piecewise constant objects, while preserving edges .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Reconstruction of the intermediate three‐dimensional activity distribution from a limited number of projections and a limited angular coverage is a challenging task. Iterative algorithms based on total variation minimization have been fairly successful for few‐view CT image reconstruction as well as for SPECT imaging . Total variation minimization encourages piecewise constant objects, while preserving edges .…”
Section: Discussionmentioning
confidence: 85%
“…Iterative algorithms based on total variation minimization have been fairly successful for few-view CT image reconstruction 23,24 as well as for SPECT imaging. 25,26 Total variation minimization encourages piecewise constant objects, while preserving edges. 27 Simulations, not presented in this paper, showed that total variation minimization did not improve nuclear image quality, since noise amplitude was larger than edge contrast.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the conventional MLEM algorithm [19,20], a MAP-EM-TV (maximum a posteriori, expectation maximization, total variation) algorithm was also used to test our argument [21,22]. The purpose of the MAP algorithm is to control noise.…”
Section: Computer Simulationsmentioning
confidence: 99%
“…The data fidelity term encourages the forward projections of the reconstruction to match the measurements, while a popular Bayesian term uses the total variation (TV) norm of the reconstruction [ 1 , 2 ]. Minimizing the TV norm encourages the image to be piecewise constant [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%